Analysis of Novel Variable Reluctance Resolver with Asymmetric Teeth on the Stator. (20th June 2013) - Liu, Chengjun; QI, Ming; Zhao, Meng
Abstract : The variable reluctance (VR) resolver is usually used to measure the shaft angle of motor. A novel VR resolver with asymmetric teeth on the stator is proposed to achieve the minimal number of active teeth and eliminate the amplitude imbalance of the output voltages of SIN and COS coils by bringing the fifth compensating tooth. The structure and the total output voltages of signal windings are explicated theoretically in detail. The topology of such a machine just requires 2D finite element analysis (FEA) to accurately predict the machine performance. Results of FEA and principle of VR resolver with asymmetric teeth are in good agreement, and several special relevant problems are studied. Finally, experimental results validate the theoretical analysis and FEA of the proposed VR resolver.